Ethnic differences in nutrition - Ordovas, Jose (Henry Stewart Talks, 2012)
Nutrition and evolution of brain development, Human diversity, Salivary amylase and starch digestion, Positive selection of lactase persistence, Food globalization, The diet-heart connection: nature versus nurture, Health disparities, Genetic predisposition, Gene-environment interactions